Cells release prions in association with exosomes - Fevrier, Benoit (National Academy of Sciences, 2004)
Prion diseases are infectious neurodegenerative disorders linked to the accumulation in the central nervous system of the abnormally folded prion protein (PrP) scrapie (PrPsc), which is thought to be the infectious agent. Once present, PrPsc catalyzes the conversion of naturally occurring cellular PrP (PrPc) to PrPsc. Prion infection is usually initiated in peripheral organs, but the mechanisms involved in infectious spread to the brain are unclear. We found that both PrPc and PrPsc were actively released into the extracellular environment by PrP-expressing cells before and after infection with sheep prions, respectively. Based on Western blot with specific markers, MS, and morphological analysis, our data revealed that PrPc and PrPsc in the medium are associated with exosomes, membranous vesicles that are secreted upon fusion of multivesicular endosomes with the plasma membrane. Furthermore, we found that exosomes bearing PrPsc are infectious. Our data suggest that exosomes may contribute to intercellular membrane exchange and the spread of prions throughout the organism.